Angiotensin‐converting enzyme 2 in the brain: properties and future directions - Xia, Huijing (Blackwell Publishing Ltd, 2008)
Angiotensin (Ang)‐converting enzyme (ACE) 2 cleaves Ang‐II into the vasodilator peptide Ang‐(1–7), thus acting as a pivotal element in balancing the local effects of these peptides. ACE2 has been identified in various tissues and is supposed to be a modulator of cardiovascular function. Decreases in ACE2 expression and activity have been reported in models of hypertension, heart failure, atherosclerosis, diabetic nephropathy and others. In addition, the expression level and/or activity are affected by other renin–angiotensin system components (e.g., ACE and AT1 receptors). Local inhibition or global deletion of brain ACE2 induces a reduction in baroreflex sensitivity. Moreover, ACE2‐null mice have been shown to exhibit either blood pressure or cardiac dysfunction phenotypes. On the other hand, over‐expression of ACE2 exerts protective effects in local tissues, including the brain. In this review, we will first summarize the major findings linking ACE2 to cardiovascular function in the periphery then focus on recent discoveries related to ACE2 in the CNS. Finally, we will unveil new tools designed to address the importance of central ACE2 in various diseases, and discuss the potential for this carboxypeptidase as a new target in the treatment of hypertension and other cardiovascular diseases.